Effects of phosphorus application on soil phosphorus forms and phoD-harboring microbial communities in an alpine grassland on the Qinghai-Tibetan Plateau - Liu, Dan; Song, Xiaoyan; Liu, Yang; Wang, Changting (Frontiers in Ecology and Evolution, 2023)
Phosphorus (P) application to terrestrial ecosystems affects not only aboveground plants but also soil P forms and phosphatase-associated microbes. The phoD gene is widespread in soil and plays an important role in P transformation. However, it is still unclear how phoD-harboring microbial communities respond to different P application rates, and the relationships between soil properties and phoD-harboring microbial community need to be better understood. In this study, the impacts of seven P application rates (0 (P0), 10 (P10), 20 (P20), 30 (P30), 40 (P40), 50 (P50) and 60 (P60) g∙m-2∙a-1) on the soil physicochemical properties, P forms and phoD-harboring microbial communities were assessed. As the results, inorganic P (i.e., Resin-Pi, NaHCO3-Pi, NaOH-Pi, HCl-Pi) and Labile-P increased firstly and then decreased with increasing P application rate, with the highest values in the P30 treatment. Soil phoD-harboring microbial community structures in low-P (P0 ~ P30) treatments were significantly different from that in high-P (P40 ~ P60) treatments. Soil phoD-harboring microbial Shannon and Simpson diversity increased firstly and then decreased with increasing P application rate, and there was a tipping point at the P application rate of 30 g∙m-2∙a-1. The Mantel test and structural equation modeling (SEM) revealed that Labile-P, NaOH-organic P (NaOH-Po) and soil pH were strongly related to the soil phoD-harboring microbial diversity indices. In conclusion, this study demonstrated that P application affected soil P forms and phoD-harboring microbes in an alpine grassland on the Qinghai-Tibetan Plateau, and there was a P application threshold for optimistic growth of phoD-harboring microbes in an alpine grassland on the Qinghai-Tibetan Plateau.